Analysis of Queueing System, Health Services, SOP, and Quality Standards on Patient Satisfaction Levels at Urangagung Health Center - Mardhiyah, Siti; Supardi, Supardi; Firdaus, Vera (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This study investigates the influence of queuing systems, health services, SOPs, and quality standards on patient satisfaction in health facilities. Using surveys, data is collected from patients through questionnaires. The analysis shows that the effectiveness of the queuing system, high-quality health services, proper implementation of SOPs, and achievement of quality standards contribute positively to patient satisfaction. These findings provide strategic recommendations for improving the management of queuing systems, health services, SOPs, and quality standards in health centers, with the aim of increasing patient satisfaction and the quality of primary health services.